Atopy phenotypes in the Childhood Asthma Prevention Study (CAPS) cohort and the relationship with allergic disease. Issue 6 (28th May 2013) - Garden, F. L.; Simpson, J. M.; Marks, G. B.; ,
Summary Background Atopy in early life is heterogeneous in timing of onset, remission and persistence and in the nature of specific sensitization to allergens. However, this heterogeneity is not well characterized. Objective Our aim was to define longitudinal phenotypes of atopy between ages 1.5 and 8 years, and to assess the relationship of the atopy phenotypes to the risk of asthma, eczema and rhinitis at 8 years of age. Methods We used latent class analysis (LCA) to define atopy phenotypes using data from skin prick tests that were performed at 1.5, 3, 5 and 8 years in participants in the Childhood Asthma Prevention Study (CAPS). Results Four phenotypes were defined: late mixed inhalant sensitization; mixed food and inhalant sensitization; house dust mite (HDM) monosensitized; and no atopy. All three atopic phenotypes were associated with asthma, eczema and rhinitis, but the strongest association, particularly for asthma, was with the mixed food and inhalant sensitization phenotype. Conclusion & clinical relevance We have used a LCA model to define atopy phenotypes empirically. The finding of a strong association between the mixed food and inhalant sensitization class and the presence of asthma and poor asthma control at age 8 years implies that food sensitization in early life may be of greater significance for subsequent risk of asthma than previously thought.